Chronic traffic noise increases food intake and alters gene expression associated with metabolism and disease in bats. Issue 10 (19th July 2020) - Song, Shengjing; Chang, Yang; Wang, Daiping; Jiang, Tinglei; Feng, Jiang; Lin, Aiqing
Abstract: Anthropogenic noise exposure has deleterious effects on the foraging ecology of many animals. However, the effects of chronic anthropogenic noise on food intake and health condition in wildlife remain largely unknown. We tested whether traffic noise exposure over multiple days would change food intake and would have effects on the health of Asian particoloured bats. We broadcast traffic noise to the bats of two noise‐exposure groups (group A, five bats; group C, six bats) and broadcast silence files to the bats of two control groups (group B, five bats; group D, six bats) for 12 days. We measured the changes in food intake, body weight and concentration of faecal triiodothyronine (T3) and thyroxine (T4) in groups A and B. We compared the transcriptional profiles in brain, kidney and liver tissues between bats in groups C and D. The bats exposed to traffic noise had a significantly higher daily food intake and a significantly greater body weight than bats in control group during the period of playback. Faecal T3 and T4 were higher in the noise‐exposure group after playback had been on for more than 1 day. We found a total of 169 differentially expressed genes (DEGs) between noise‐exposure and control groups. Some DEGs related to stress response were upregulated in the bats exposed to noise. The 169 DEGs were mainly enriched in Gene Ontology (GO) terms associated with metabolism, fundamental cellular processes, stress response and immune response. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways affected by noise exposure were linked with metabolism, disease, apoptosis, autophagy, phagosome and ribosome. Synthesis and applications . Our results suggest that bats exposed to chronic traffic noise while roosting may need more energetic intake and have a greater motivation to forage than others not exposed to noise, probably as a result of a stress response. Furthermore, chronic traffic noise may increase the risk of metabolic dysregulation, immune disorders and other diseases. Management measures for reducing noise disturbance, for example, implementing sound barriers, are essential. Abstract : Our results suggest that bats exposed to chronic traffic noise while roosting may need more energetic intake and have a greater motivation to forage than others not exposed to noise, probably as a result of a stress response. Furthermore, chronic traffic noise may increase the risk of metabolic dysregulation, immune disorders and other diseases. Management measures for reducing noise disturbance, for example, implementing sound barriers, are essential. 中文摘要: 人为噪声对许多动物的觅食产生消极影响。但是，长时间的人为噪声曝露对野生动物的摄食量和健康状况的影响在很大程度上仍是未知。 本研究以东方蝙蝠（ Vespertilio sinensis ）为研究对象，检验交通噪音是否改变蝙蝠的摄食量，是否影响它们的健康状况。我们进行了12天的噪音回放实验，给实验组蝙蝠（A 组：5只，C组：6只）回放交通噪音，给对照组蝙蝠（B组：5只，D组：6只）回放空白文件。实验期间，监测了A组和B组蝙蝠的摄食量、体重、以及粪便中三碘甲状腺原氨酸（triiodothyronine：T3）和甲状腺素（thyroxine：T4）浓度的变化。分析了C组和D组蝙蝠的脑、肾脏和肝脏组织的基因表达差异。 结果表明，与对照组相比，实验组蝙蝠的日摄食量和体重显著增加。噪音回放一天之后，实验组蝙蝠的粪便中T3和T4的浓度均升高。 共检测到实验组和对照组蝙蝠169个差异表达基因（differentially expressed genes：DEGs），实验组蝙蝠一些与应激反应相关的DEGs表达上调。Gene Ontology富集分析结果表明，噪音诱导的169个DEGs主要与新陈代谢、细胞基础过程、应激反应和免疫应答相关。Kyoto Encyclopedia of Genes and Genomes通路分析表明，噪音影响新陈代谢、疾病、细胞凋亡、自噬、吞噬体以及核糖体相关的通路。 总结与应用：本研究结果表明，栖息在交通噪音环境中的蝙蝠可能需要摄取更多的能量或具有更强的捕食动机，这很可能是对噪音的应激应答结果。此外，长时间交通噪音暴露可能增加个体体内代谢失调、免疫紊乱和其他疾病的风险。建议采取必要的管理措施，如使用声屏障，以减少噪音干扰。